2013
DOI: 10.3390/ijms14059820
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effect of Ginsenoside Rg5 in Lipopolysaccharide-Stimulated BV2 Microglial Cells

Abstract: Microglia are resident immune cells in the central nervous system. They play a role in normal brain development and neuronal recovery. However, overactivation of microglia causes neuronal death, which is associated with neurodegenerative diseases, such as Parkinson’s disease and Alzheimer’s disease. Therefore, controlling microglial activation has been suggested as an important target for treatment of neurodegenerative diseases. In the present study, we investigated the anti-inflammatory effect of ginsenoside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 36 publications
0
48
0
Order By: Relevance
“…The transcription factor NF- κ B, widely expressed in the nervous system, plays a leading role in LPS-induced inflammatory responses [15]. In this study, we noted that NF- κ B activation was dramatically induced by LPS stimulation, while salidroside regulates microglial activation by inhibiting the I κ B α degradation and phosphorylation of I κ B α and p65, a subunit of NF- κ B.…”
Section: Discussionmentioning
confidence: 74%
“…The transcription factor NF- κ B, widely expressed in the nervous system, plays a leading role in LPS-induced inflammatory responses [15]. In this study, we noted that NF- κ B activation was dramatically induced by LPS stimulation, while salidroside regulates microglial activation by inhibiting the I κ B α degradation and phosphorylation of I κ B α and p65, a subunit of NF- κ B.…”
Section: Discussionmentioning
confidence: 74%
“…In addition, elevated H 2 O 2 due to SOD upregulation leads to the activation of mitogen‐activated protein kinase (MAPK), which decreases the levels of the antiapoptotic factor Mcl1, resulting in apoptotic cell death . The transcription factor NF‐κB plays a leading role in the inflammatory response . TCDD activates MAPK, triggering subsequent redox imbalance through CYP1A1 expression .…”
Section: Discussionmentioning
confidence: 99%
“…Data have shown that activated microglia change their morphology, proliferate and enhance the expression of distinctive surface molecules such as CD40 and MHC II. Furthermore, activation of microglia results in the release of various proinflammatory cytokines such as IL1b, IL-18, TNF-a, and IL-6, as well as neurotoxic mediators like nitric oxide (NO), prostaglandin (PG) E2 and superoxide anion (Jana et al 2007;Lee et al 2013).…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…Data have shown that activated microglia change their morphology, proliferate and enhance the expression of distinctive surface molecules such as CD40 and MHC II. Furthermore, activation of microglia results in the release of various proinflammatory cytokines such as IL1b, IL-18, TNF-a, and IL-6, as well as neurotoxic mediators like nitric oxide (NO), prostaglandin (PG) E2 and superoxide anion (Jana et al 2007;Lee et al 2013).It should be noted that many factors trigger pathological microglial activation. One such factor is experimental exposure to a primary component of endotoxin from Gramnegative bacteria cell walls, lipopolysaccharide (LPS) (Kettenmann et al 2011).…”
mentioning
confidence: 99%